A comparative study of surface modification under helium implantation on mechanically and electrochemically polished tungsten. Issue 1 (2nd January 2021) - Chen, Zhehao; Meng, Xuan; Zhao, Jiangtao; Guan, Xingcai; Wang, Qiang; Lv, Peng; Guan, Ming; Wang, Tieshan
ABSTRACT: Tungsten is widely used as a plasma-facing material in nuclear fusion reactors due to its favorable properties; however, the extensive exposure of energetic particles could lead to severe degradations on its surface. Therefore, we studied the surface modification resulted from helium implantation on the mechanically and electrochemically polished tungsten at an elevated temperature. Samples of both types were implanted with 18 k e V helium ions to a fluence of 1.8 × 10 18 H e ⋅ c m − 2 at 1073 K . Compared with electrochemically polished tungsten, fewer and smaller blisters was identified on mechanically polished sample by means of scanning electron microscopy (SEM). Combined with the focused ion beam (FIB) facility, cross-sectional SEM and transmission electron microscopy (TEM) analyses were conducted, and elongated cavities along the grain cracks were confirmed in the mechanically polished sample. Both SEM and TEM observations confirmed that these cavities can connect the damaged layer and sample surface, and effectively exhaust the accumulated He gas. Subsequently, the possible correlation between blistering reduction and the helium-induced cavities in mechanically polished tungsten was discussed.